The use of ceftriaxone impregnated beads in the management of chronic osteomyelitis (Faculty of Medicine Universitas Indonesia, 2005)
Up to now, orthopaedic management of chronic osteomyelitis is still problematic. Debridement and antibiotic administration is still a widely practiced management. However, oral or parenteral antibiotics often cannot reach the infection site well. Some experts have developed a system to administer local antibiotic in the form of antibiotic beads. Antibiotic beads on the market are still very expensive. Therefore, we made efforts to make our own antibiotic beads by using Ceftriaxone as the antibiotic. Ceftriaxone impregnated beads were made by mixing 2 grams of Ceftriaxone powder with 40 grams of polymethyl methacrylate (PMMA) bone cement sterilely. The size of the beads was 3 x 5 mm. Thirty male rabbits that were induced to get osteomyelitis by inoculating Staphylococcus aureus to their left radius bones were used. In the fourth week, clinical, radiological, histological examination and bacterial culture were performed to prove the presence of osteomyelitis. Then, the samples were divided into 3 groups of ten. The first group only underwent debridement. The second group underwent debridement followed by intravenous Ceftriaxone administration. The third group underwent debridement followed by intravenous Ceftriaxone and Ceftriaxone-impregnated beads administration. After four weeks, clinical, radiological, histological examination and bacterial culture were repeated. In the first group, the incidence rate of osteomyelitis at the end of the fourth week of therapy was 60% (success rate 40%). In the second group, after four weeks of therapy the incidence rate of osteomyelitis after treatment was 20% (success rate 80%), whereas that of the third group was 0% (success rate 100%). In conclusion, the efficacy of combination of systemic antibiotic therapy and ceftriaxone impregnated beads in the therapy of chronic osteomyelitis is better than systemic antibiotic therapy. (Med J Indones 2005; 14: 157-62)